Timelines of local authorities financial reports / Norkhazimah Ahmad and Asmah Abdul Aziz - Ahmad, Norkhazimah; Abdul Aziz, Asmah (Faculty of Accountancy, 2005)
This study examines audit lags of local authorities in Johor from 1990 to 2001. In addition, it also investigates the association of audit lag with functioning pattern of local authorities from 1999 to 2001. This three-year period has been chosen, because of the several changes which have been adopted by the local authorities in Johor within this period. Audit lag is defined, as the gap in terms of number of months from the end of the financial year (31 December) to the signature date of audit certificate by the Auditor General. Data of audit lags were gathered from the financial statements and audit certificates issued by the Auditor General, which were obtained from the National Audit of Johor branch. Analysis of this study reveals that 88.89% of audit lags of local authorities in Johor within the period of study exceeded 12 months. The longest average audit lag was in 1990 and the shortest was in 1995. Analysis of association of audit lag and functioning of Johor local authorities from 1999 to 2001 reveals that, only certain local authorities were significantly associated with audit lags.